2010
DOI: 10.1007/s00464-010-1246-0
|View full text |Cite
|
Sign up to set email alerts
|

Mesh shrinkage and pain in laparoscopic ventral hernia repair: a randomized clinical trial comparing suture versus tack mesh fixation

Abstract: Transfascial sutures are associated with more pain within the first 6 postoperative weeks and less mesh shrinkage after 6 months compared with mesh fixation using metal tacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
98
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 19 publications
2
98
0
6
Order By: Relevance
“…First a sufficient overlap of the mesh and second the mesh fixation. We showed a significant decrease in horizontal mesh size after tack fixation (mean difference -3.1% ±3.9%) versus fixation using sutures (-0.1% ±2.3%; p=0.018) [26]. Mean vertical mesh size was not significantly different between the two groups: tack fixation -2.8% ±6.1%, suture fixation -0.7% ±4.1% (p=0.16).…”
Section: Recurrence Ratementioning
confidence: 73%
See 4 more Smart Citations
“…First a sufficient overlap of the mesh and second the mesh fixation. We showed a significant decrease in horizontal mesh size after tack fixation (mean difference -3.1% ±3.9%) versus fixation using sutures (-0.1% ±2.3%; p=0.018) [26]. Mean vertical mesh size was not significantly different between the two groups: tack fixation -2.8% ±6.1%, suture fixation -0.7% ±4.1% (p=0.16).…”
Section: Recurrence Ratementioning
confidence: 73%
“…Pain after mesh fixation with transfascial sutures is likely due to nerve irritation or entrapment and the relatively small distance between individual sutures used in this study. The significant reduction of pain between 6 weeks and 6 months post operation in these patients could be in response to desensitisation of entrapped nerve fibres or in response to resolution of local inflammation [26]. Asencio et al showed in their study that 22% of the laparoscopic group and 7% of the open group reported significantly pain three months after the operation [13].…”
Section: Enterocutaneous Fistulamentioning
confidence: 89%
See 3 more Smart Citations